2020
DOI: 10.1016/j.bonr.2019.100234
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyponatremia in patients with proximal femoral fractures after low energy trauma: A retrospective study in a level-1 trauma center

Abstract: IntroductionWe evaluated the prevalence and influence of chronic hyponatremia in patients with low energy trauma. We also investigated the influence of medication and diseases on hyponatremia.Material and methodsThis retrospective study included 314 cases of proximal femoral fracture due to low energy trauma. Patients were treated in the University Medical Center Goettingen within 3 years. Hyponatremia was defined as serum sodium <135 mmol/L at admission.ResultsOverall, 15.6% of patients in the low energy trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Another limitation of the study is that the influence of medications on sodium levels in the patient population was not considered as has been investigated in several previous studies [8,13,18,[25][26][27][28]. These studies reported, for example, that aldosterone antagonists and sartans have a significant impact on hyponatremia of patients [29] as has also been observed with selective serotonin re-uptake inhibitors (SSRIs) and thiazide, all of which induce hyponatremia [30][31][32][33][34]. This aspect concerning the influence of possible medication on hyponatremia and its subsequent effect on low-energy trauma fractures is not reflected in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the study is that the influence of medications on sodium levels in the patient population was not considered as has been investigated in several previous studies [8,13,18,[25][26][27][28]. These studies reported, for example, that aldosterone antagonists and sartans have a significant impact on hyponatremia of patients [29] as has also been observed with selective serotonin re-uptake inhibitors (SSRIs) and thiazide, all of which induce hyponatremia [30][31][32][33][34]. This aspect concerning the influence of possible medication on hyponatremia and its subsequent effect on low-energy trauma fractures is not reflected in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria: (i) age 60–90 years; (ii) acute OVCF (<2 weeks 29 ) from low energy trauma (fall from a standing height or less 30 , 31 ); (iii) patients suffering from severe back pain; (iv) only underwent either rhPTH or VAP treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria: (i) age 60-90 years; (ii) acute OVCF (<2 weeks 29 ) from low energy trauma (fall from a standing height or less 30,31 Finally, 22 patients who received rhPTH treatment (rhPTH group) and 49 patients who underwent VAP (VAP group) were included in this study. All the patients' data were collected and measured by two experienced orthopaedic surgeons (T. Z. and G. G).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…I nstitutional review board approval was obtained to perform a retrospective review of clinical registry data for patients undergoing TJA (total hip or knee arthroplasty) at a large, tertiary academic institution between 2016 and 2019. Consecutive patients undergoing TJA who had preoperative and postoperative serum sodium concentration data, among other a priori-determined variables of interest based on prior literature, were deemed eligible for inclusion (Table I) 1,[16][17][18] . Preoperative sodium levels were measured within 1 week of surgery, while postoperative levels were measured within 24 hours of surgery.…”
Section: Patient Selectionmentioning
confidence: 99%